2013
DOI: 10.1371/journal.pone.0077663
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cluster of HIV-1 Controllers Infected with Low Replicating Viruses

Abstract: Long term non-progressor patients (LTNPs) are characterized by the natural control of HIV-1 infection. This control is related to host genetic, immunological and virological factors. In this work, phylogenetic analysis of the proviral nucleotide sequences in env gene from a Spanish HIV-1 LTNPs cohort identified a cluster of 6 HIV-1 controllers infected with closely-related viruses. The patients of the cluster showed common clinical and epidemiological features: drug user practices, infection in the same city (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 61 publications
(80 reference statements)
3
39
0
Order By: Relevance
“…However, the relationship between viral loads and entry efficiency lost significance at 12 mpi, suggesting that other factors, such as immune responses, could be influencing the association during later stages of infection. Overall, our results support the findings of Lassen et al, (2009) and Casado et al, (2013) who found that entry efficiency of viruses from seven ES and three LTNP, respectively were lower than those from chronic progressors, suggesting that viruses with poor entry could lead to viral control. In support, one of our PSV clones, 398, a LTNP with longitudinal viral loads below 2000 copies/ml (Casado et al, 2010) had the lowest entry efficiency.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…However, the relationship between viral loads and entry efficiency lost significance at 12 mpi, suggesting that other factors, such as immune responses, could be influencing the association during later stages of infection. Overall, our results support the findings of Lassen et al, (2009) and Casado et al, (2013) who found that entry efficiency of viruses from seven ES and three LTNP, respectively were lower than those from chronic progressors, suggesting that viruses with poor entry could lead to viral control. In support, one of our PSV clones, 398, a LTNP with longitudinal viral loads below 2000 copies/ml (Casado et al, 2010) had the lowest entry efficiency.…”
Section: Resultssupporting
confidence: 91%
“…Pseudovirions (PSVs) were generated to determine the effect of entry efficiency on viral load and to identify phenotypic properties that could influence this relationship. The only LTNP of this study had the lowest entry efficiency supporting the two previous studies that showed that viruses from HIV LTNP and ES had lower entry efficiency compared to chronic progressors (Lassen et al, 2009;Casado et al, 2013). We thus wanted to determine the impact of entry efficiency of T/F PSVs on viral loads from progressors subsequent to transmission.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Intrasample diversity was estimated by the best-fit model of nucleotide substitution in the MEGA 6 program. An estimation of viral infection time or "viral dating" was deduced, assuming a relaxed molecular clock, from the genetic distance of the nucleotide sequence of each subject virus to the MRCA (most recent common ancestor) of the HIV-1 Spanish epidemic (6,10,11,66).…”
Section: Methodsmentioning
confidence: 99%